Authorial and Non Authorial Affect in Speech: An Appraisal Theory Approach - Dwi Meisyitah Ananda; M. R. Nababan; Riyadi Santosa (Universitas Muhammadiyah Semarang, 2018)
This study deals with authorial and non-authorial affect in speech. The aim is to find out the types of affect, graduation and engagement. This study used descriptive qualitative approach. The data were obtained through content analysis from speech transcript. The data was analyzed by using domain, taxonomy, and componential analysis. The result shows that there are 10 types of affects found in authorial affect, 13 types of affects found in non-authorial affect, and 10 types of affects found in authorial-non-authorial affect. Authorial affects and combinations are used more frequently than non-authorial It indicates that the speaker as first person often expresses his/her own feelings and also expresses his/her and others’ feeling upon something.